2011
DOI: 10.4103/0975-3583.78585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of percutaneous renal revascularization with stent placement in hypertension among patients with atherosclerotic renovascular diseases

Abstract: Aim:The aim was to assess the effect of renal angioplasty with stent on systolic, diastolic, and mean arterial blood pressure (MAP) in awake and sleep time with ambulatory blood pressure (ABP) monitoring (Holter monitoring).Materials and MethodsPatients with angiographically proven atherosclerotic renal artery stenosis (RAS) were referred to the Angiography Department of Imam Hospital for intervention during a 1-year period from June 2008 to December 2009. Primary stent placement was attempted by a single oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…The effectiveness of angiotensin-converting enzyme and angiotensin II receptor blockers has made it easy to control blood pressure in patients with RVH [ 11 ]. On the other hand, several studies showed the effectiveness of PTRA with or without stent placement [ 12 , 13 ]. A prospective study investigating the efficacy of stent revascularization for the prevention of cardiovascular and renal events among patients with renal artery stenosis is ongoing [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of angiotensin-converting enzyme and angiotensin II receptor blockers has made it easy to control blood pressure in patients with RVH [ 11 ]. On the other hand, several studies showed the effectiveness of PTRA with or without stent placement [ 12 , 13 ]. A prospective study investigating the efficacy of stent revascularization for the prevention of cardiovascular and renal events among patients with renal artery stenosis is ongoing [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,15,23,25 Além da hipertensão arterial, a estenose de artéria renal, especialmente quando a etiologia é ateroscleró-tica, pode causar insuficiência renal, principalmente quando a estenose é bilateral, por meio da nefropatia isquêmica crônica. 6,26 Tal complicação pôde ser também observada em nosso estudo, visto que alguns pacientes já estavam em tratamento conservador para doença renal crônica e alguns outros já apresentavam alterações dos níveis séricos de creatinina, indicando uma possível evolução desfavorável da função renal. Estima-se que cerca de 12% a 16% dos pacientes com insuficiência renal crônica terminal tenham como causa de lesão renal a estenose de artéria renal, provocando nefropatia isquêmica, principalmente quando a estenose é bilateral [27][28][29] .…”
Section: Doença Aterosclerótica Multiarterial Em Pacientes Hipertensosunclassified